Optimizing Household Financial Management Based on Financial Literacy in Gintung Village, Sukadiri District - Lahmudin Li Aziz; Reza Fahlevi Nurpaiz (International Research and Development for Human Beings (IRDH), 2025)
Household financial management is a crucial aspect of maintaining family economic stability, particularly in rural areas where most residents rely on irregular income sources. Low financial literacy often leads to unplanned consumption patterns, a lack of a savings culture, and dependence on consumptive debt. Responding to this issue, a community service program was conducted in Gintung Village, Sukadiri District, Tangerang Regency, in August through a financial literacy seminar. The program aimed to equip households with the knowledge and practical skills necessary to manage their finances more effectively. The methods involved interactive seminars, group discussions, and simple financial recording simulations. Participants included household representatives such as farmers, daily laborers, small traders, and housewives. The results indicated significant improvement in participants’ understanding of financial literacy concepts, such as differentiating between needs and wants, preparing a household budget, and allocating funds for emergencies and savings. Furthermore, the program encouraged new habits within families, including recording household cash flow and discussing financial matters collectively. This practice is expected to contribute to the long-term well-being of the community. Therefore, the program serves as a practical model of financial literacy education at the community level that can be replicated in other rural areas.